Immunomodulatory activity of kersen leaf extract (Muntingia calabura) on diabetic rats: analysis of immune response - Fonnie Esther Hasan; Reni Yunus; Magdalena Magdalena (Universitas Nahdlatul Ulama Surabaya, 2024)
The immune response to high blood glucose levels leads to an inflammatory response and also produces inflammation mediators. Immunomodulatory functions of Kersen (Muntingia calabura) need further enhancement to ensure that its benefits are more widely recognized by the public. This study aims to determine the immunomodulatory activity of Kersen leaf in inducing and modulating the immune response in diabetic rats. This study was an experimental laboratory with a pre-and post-test with a control group design. The subjects were 30 white rats (Rattus Novergicus Wistar Strain), were treated with extract M. calabura dose 1 (100 mg/kg bw/day), dose 2 (200 mg/kg bw/day), dose 3 (300 mg/kg bw/day). For clinical evaluation, three control groups were formed, including a Normal Control Group, a Diabetes Mellitus (DM) Positive Group, and a DM Positive Group treated with Anti-Diabetic Drugs. The highest amount of IFN-γ concentrations were found in the DM positive control group + antidiabetic drugs (710.3 ± 27.2 ng/mL). The highest number of Nitrit Oxide (NO) concentration was found in the DM positive control group (103.7 ± 10.2 µmol/L). The highest average amount of pancreatic β cell regeneration was found in the normal control group. The DM positive control group and the treatment group had a significant difference (p < 0.05) It means that there is a significant difference in the data of all treatment groups, or these three groups have anti-diabetic activity by repairing or preventing damage to the pancreas organ in DM rats. This study revealed that M. calabura possesses immunomodulatory activity, capable of inducing and modulating immune responses in diabetic rats.